IMPROVING THE FINANCING MECHANISM OF PRESCHOOL EDUCATION INSTITUTIONS IN UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper explores the current state and challenges of financing preschool education institutions in Uzbekistan. It proposes strategic recommendations to enhance the existing financial model to ensure equity, accessibility, and quality. The study employs a qualitative analysis of policy documents, financial reports, and international best practices to formulate a practical framework for sustainable financing in the preschool education sector.